The mediation role of trust on the effect of commitment to religiosity and marketing communication on customer loyalty of islamic banks - Fadila, Dewi; Lupikawaty, Marieska; Africano, Fernando (International Journal of Communication and Society, 2022)
very important to create customer trust and loyalty. With a high commitment to religiosity and marketing communication, it can maintain loyalty because of customer trust in Islamic banks. The purpose of this study was to determine the effect of commitment to religiosity and marketing communication on the loyalty of Islamic bank customers with trust as a mediating variable. This research is a quantitative research. Data collection was carried out using a survey to research respondents, namely customers of Islamic banks in the city of Palembang. In this study, the Slovin formula was used for sampling with stratified random sampling, this is because the authors distributed questionnaires only in one period of time so that each element/member of the population did not have the same opportunity to be selected as samples. The sample in this study were 400 samples. The data analysis technique in this study uses SEM (Structural Equation Modeling) analysis which is operated through the AMOS program. Research shows that commitment to religiosity and marketing communication has an effect on trust. Commitment to religiosity, marketing communication and trust affect customer loyalty. Trust mediates the effect of religious commitment and marketing communication on customer loyalty.